Das Marmordach des Tempels A in Selinunt - Knechtel, Miriam (Römische Mitteilungen, 2024)
The high architectural quality of Temple A, built around the middle of the 5th century BC on the southern acropolis of Selinunte, is also made evident by its marble roof of which numerous fragments are still preserved. These finds, largely kept in the Museo Archeologico Regionale Antonino Salinas in Palermo, include blocks of the sima embellished with lion-head waterspouts, pieces of flat and cover tiles, as well as fragments of the figural decoration for the building. Based on a detailed documentation of the material, the reconstruction suggested by Gabrici could be corroborated more exactly in places, so that the roof can now be visualized almost completely. This restoration contributes to the research into construction details and the conceptual background of the roof and its related temple, but also facilitates a better understanding of the emergence and development of marble roofs in the Greek West and their relationship to designs, constructions and also craftsmen from the Greek mainland.